Salt licks and adventurous tourists: A framework for sustainable ecotourism - Ang, Sek Chuan; Chan, Ngai Weng; Jabil Mapjabil, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2012)
The objective of this study is to survey the demographic patterns of visitors to salt licks in Malaysia to determine whether there is any clear management direction for salt lick ecotourism in the country. Only respondents who had been to at least one salt lick in Malaysia were invited to do the survey. Survey forms were used in all the salt lick areas visited by the authors. In addition, emails were sent to invite participants to do the online survey. Data gathered from both surveys were tabulated using MS Excel software. The results showed that salt licks’ visitors were more inclined to seek adventurous activities, were budget conscious, enjoyed nature and chose camping as the favourite accomodation. Watching wildlife was not as important for them as initially perceived but the experiences of visiting salt lick was. This study showed that the management plan for salt lick areas development should target the budget conscious- cum-adventurous tourists rather than catering to the willing-to-pay but rather unsustainable mass casual tourists, as this would reduce wastage and stress to natural heritage areas.